DINAMIKA PERAN PEREMPUAN SUNDA DALAM KEPEMIMPINAN POLITIK ERA MODERN - Amanah, Dini Asmiatul; Nurbayani, Siti; Komariah, Siti; Nugraha, Restu Adi (Jurnal Analisa Sosiologi, 2023)
The involvement of women in politics is crucial for democracy. In the mythology and philosophy of Sundanese culture, women have a respected role and status in society that is equal to men. However, with the emergence of patriarchal culture during feudalism, women were placed as a subordinate class and men were deemed more suitable for leadership and decision-making in public affairs. This research examines the positive shift in social construction and Sundanese values regarding the leadership of Sundanese women and their role in modern politics. The research method used is a qualitative approach with a descriptive approach. Data collection was conducted through interviews with legislators, observation, and literature studies. The results show that in the modern era, there has been a positive shift in the social construction and cultural values of women's leadership in the political sphere. The public's view is becoming more open that women can be good leaders in the public domain, supported by the performance of Sundanese women legislators who exhibit political values such as awareness, openness, consultation, and flexibility in communication. However, Sundanese women still face obstacles in entering politics, especially issues of courage and self-confidence. Therefore, efforts are needed to increase awareness, knowledge, and skills of women in politics through the community, education, and organizations that support women as political leaders.Keywords: Leadership, Politics, Women, Sundanese AbstrakKeterwakian perempuan dalam ranah politik merupakan hal yang penting bagi demokrasi. Dalam mitologi dan filosofi kebudayaan Sunda, perempuan Sunda memiliki peran dan kedudukan terhormat dalam masyarakat yang setara dengan laki-laki. Namun, seiring masuknya budaya patriarki pada masa feodalisme, menempatkan perempuan sebagai subjek kelas dan laki-laki yang lebih layak menjadi pemimpin dan decision making dalam urusan publik. Penelitian ini mengkaji pergeseran konstruksi sosial dan nilai-nilai kesundaan dalam kepemimpinan perempuan sunda dan peran perempuan sunda dalam politik era modern. Metode penelitian yang digunakan adalah metode kualitatif dengan pendekatan deskriptif. Pengumpulan data dilakukan melalui wawancara dengan anggota legislatif, observasi dan studi literatur. Hasilnya bahwa di era modern, terjadi pergeseran positif dalam konstruksi sosial budaya mengenai kepemimpinan perempuan di dunia politik. Pandangan masyarakat semakin terbuka bahwa perempuan dapat menjadi pemimpin yang baik di ranah publik, yang didukung oleh kinerja anggota legislatif perempuan Sunda yang menunjukkan nilai-nilai politik seperti kesadaran, keterbukaan, musyawarah, dan fleksibilitas dalam berkomunikasi. Meskipun demikian, perempuan Sunda masih menghadapi kendala dalam memasuki dunia politik, terutama masalah keberanian dan kepercayaan diri. Oleh karena itu, diperlukan upaya untuk meningkatkan kesadaran, pengetahuan, dan keterampilan perempuan dalam politik melalui lingkungan masyarakat, pendidikan, dan organisasi yang mendukung perempuan sebagai pemimpin politik.Kata Kunci: Kepemimpinan, Politik, Perempuan, Sunda